Rainfall erosivity indices in the Goiânia region, Goiás State, Brazil - Silva, Marx Leandro Naves (1997)
The measure of rainfall erosive potential is becoming object of many studies, since this parameter is indispensable in the studies of models for the prediction of soil losses through hydrical erosion. This study was carried out at EMGOPA/Embrapa-CNPS experimental station, to determine the rainfall erosivity for the Goiânia region, GO, Brazil, through rainfall graphical data. The rainfall annual average erosivity for the region was 8353.0 MJ mm ha-1 h-1 year-1 and 129.8 MJ ha-1 year-1, respectively for EI30 and KE>25. The correlation coefficients showed that the rainfall and rainfall coefficient allow to estimate the rainfall erosivity in the absence of more complete rainfall data. The erosion critical period, due to the occurrence of erosive rainfalls is from September to February, when 85.70% and 84.05% of the KE>25 and EI30 annual total, respectively, occurr. In this period, conservation practices are necessary in order to reduce the hydrical erosion, for the maintenance of soil sustainability.